Estratégias de inibição, mecanismos moleculares e interações intermoleculares em complexos macromoleculares - Murakami, Mario Tyago [UNESP] (2006)
This work presents some features of essential biological processes such as the haemostatic system, integrity of biological membranes and thermostability of proteins. Crystallographic, spectroscopic and in silico tools have been used to obtain information at the molecular level of macromolecular complexes, action mechanisms and inhibition pathways. Worms, snakes, ticks, leeches and spiders produce a variety of proteins, which interfere in the regulation of these systems. Different toxins isolated from these organisms were characterized providing necessary information for the development of a new anti-myonecrotic molecule and reveal a new factor Xa exosite that is important for macromolecular substrates recognition and inhibition. The first crystal structure of a member of the sphingomyelinases D family was determined by the quick cryo-soaking technique and the catalytic mechanism was proposed, which involves a magnesium-binding site and two catalytic histidines. An alternative activation of the protein C pathway that does not require thrombomodulin was structurally characterized and revealed the dual role of the elestrotatic surface charge around the active site and the three strategically positioned carbohydrate moieties in the approach, recognition and activation of protein C.